Peningkatan Value Added Ikan Lele menjadi Produk Mi di Desa Mekar Sari Kecamatan Maro Sebo Ulu - Hastuti, Dwi; Hardiani; Hodijah, Siti; Yulmardi; Rahmadi, Selamet (Studium: Jurnal Pengabdian Kepada Masyarakat, 2023)
The culinary business in Jambi Province, including Batang Hari Regency, continues to be developed as an effort to increase the consumption of fish and improve income. The abundance of resources in Mekar Sari Village, particularly in terms of catfish, presents a significant opportunity to enhance its value added by transforming it into catfish noodles. Additionally, catfish can be cultivated rapidly and in sufficient quantities, making it a promising raw material resource. With a sizable market share, noodles are a widely preferred food. Catfish-based noodle products have a vast market potential due to the increasing demand for noodles. In the food business, product diversification takes the form of catfish noodles, providing customers with new options. Noodles made from catfish add value to the end product. Catfish noodles can offer additional nutritional benefits to consumers as catfish is a rich source of protein, vitamins, and essential minerals for human health. By increasing the financial value of their catch, catfish producers can gain greater influence. This can enhance the well-being of catfish farmers by increasing their income. Transforming the added value of catfish into noodles opens up new business prospects, boosts the income of catfish breeders, and contributes to the growth of a sustainable fisheries industry.